2022
DOI: 10.1021/acs.energyfuels.2c01828
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of High-Performance Porous Carbon Materials by Citric Acid-Assisted Hydrothermal Carbonization of Bamboo and Their Application in Electrode Materials

Abstract: Renewable energy needs an environmentally friendly and efficient energy storage device. In this work, porous carbon materials with different properties are prepared by citric acid (CA)-assisted hydrothermal carbonization of bamboo and KOH activation. The effects of the ratio of the added CA on the structure of hydrochar and the porous carbon product are studied systematically. It is found that the added CA can improve the carbonization degree of the hydrochar, content of oxygencontaining functional groups, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 56 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…These acids interact with mineral compounds, impacting hydrolysis, dehydration, condensation, and polymerization processes, making the process autocatalytic [49]. Further, citric acid may introduce more functional groups into the carbon skeleton and remove some minerals and organic groups in the biomass feedstock, leading to more rough and porous structures [50,51]. Faradilla et al [52] showed that the addition of citric acid during the HTC treatment of cellulose nanofiber and softwood pulp increased the diameter of formed carbon spheres.…”
Section: Catalystmentioning
confidence: 99%
“…These acids interact with mineral compounds, impacting hydrolysis, dehydration, condensation, and polymerization processes, making the process autocatalytic [49]. Further, citric acid may introduce more functional groups into the carbon skeleton and remove some minerals and organic groups in the biomass feedstock, leading to more rough and porous structures [50,51]. Faradilla et al [52] showed that the addition of citric acid during the HTC treatment of cellulose nanofiber and softwood pulp increased the diameter of formed carbon spheres.…”
Section: Catalystmentioning
confidence: 99%
“…The resultant hydrochar had a higher calorific value and energy density, making it suitable for biofuel applications. Chen et al [54] used bamboo powder as raw material and activated the product in citric acid solution under hydrothermal conditions at 180 • C for 6 h. Citric acid is an efficient HTC additive to improve the carbonization degree, to optimize the pore structure distribution, and to introduce more oxygen-containing functional groups (OFGs) to hydrochar, which offer an appropriate precursor to be activated by KOH to improve the specific surface area (SSA) level and electrochemical performance of the activated porous carbon.…”
Section: Htc Using Catalystsmentioning
confidence: 99%
“…A possible solution is adding additives to the HTC process which can greatly enhance their electrochemical characteristics and offer a solid choice for creating superior SCs. To put it in practical terms, Chen et al [28] described the fabrication of porous carbon materials by adding citric acid (CA) to help the HTC of bamboo, which considerably boosted the SSA (3132 m 2 g -1 ) and the specific capacitance (435.5 F g -1 at the current density of 0.5 A g -1 ) of EMs. A similar method was utilized by Susanti et al [29] to synthesis porous carbon materials.…”
Section: Hydrothermal Carbonizationmentioning
confidence: 99%